Longitudinal analysis of vaginal microbiota during IVF fresh embryo transfer and in early pregnancy - Sofia Väinämö; Schahzad Saqib; Ilkka Kalliala; Kaisa Kervinen; Kaisu Luiro; Maarit Niinimäki; Mervi Halttunen-Nieminen; Seppo Virtanen; Pekka Nieminen; Anne Salonen; Tiina Holster (Microbiology Spectrum, 2023)
ABSTRACT Non-Lactobacillus-dominated vaginal microbiota has been associated with poor gynecologic health and complications during pregnancy. Lactobacilli and especially Lactobacillus crispatus associate with good reproductive health and dominate the microbiota during healthy pregnancy. We examined whether the composition of vaginal microbiota at the time of fresh embryo transfer (ET) has an impact on the success of in vitro fertilization (IVF) and whether vaginal microbiota changes from IVF-ET to early pregnancy within individuals. Vaginal swab samples were collected from subfertile women at the time of IVF-ET (n = 76) and at the eighth gestational week (n = 21) from those who achieved clinical pregnancy. The microbiota composition was analyzed using 16S rRNA gene amplicon sequencing. L. crispatus was more abundant among the 30 women who achieved clinical pregnancy (46.9% vs. 19.1%, q = 0.039) and the 26 women who had live birth (43.3% vs. 23.1%, q = 0.32) compared to those who did not. Lactobacilli, mainly L. crispatus (76.2%), dominated all early pregnancy samples. Microbiota remained the same, i.e., Lactobacillus-dominated type in 52% (11/21), shifted from one Lactobacillus-dominated type to another in 24% (5/21), or shifted from mixed community to Lactobacillus-dominated type in 24% (5/21) women, but never from Lactobacillus dominance to non-lactobacilli dominance. Our results emphasize the role of L. crispatus in the success of IVF-ET and in early pregnancy. During pregnancy, the microbiota shifted toward L. crispatus dominance even if it was undetectable before pregnancy, indicating that most women hold a reservoir of this beneficial Lactobacillus in their reproductive tract. IMPORTANCE Infertility is a global public health issue which leads many couples to seek fertility treatments, of which in vitro fertilization (IVF) is considered to be the most effective. Still, only about one-third of the women achieve live birth after the first IVF embryo transfer (IVF-ET). Factors affecting embryo implantation are poorly known, but the female reproductive tract microbiota may play a key role. Our study confirms the beneficial role of vaginal lactobacilli, especially Lactobacillus crispatus, in the probability of achieving clinical pregnancy and live birth following IVF-ET. Our findings regarding the intra-individual shift of vaginal microbiota between non-pregnancy and pregnancy states are novel and provide new information about the dynamics of microbiota in the early steps of human reproduction. These findings may help clinicians in their attempts to optimize the conditions for ET by microbiota screening or modulation and timing the ET when the microbiota is the most favorable.